Multicultural-Based Curriculum Conception - Asmuki; Achmad Yusuf; Abdul Aziz; Salim (Universitas Yudharta Pasuruan, 2020)
This study aims to describe about 1) Classification of multicultural-based curriculum in various points of view, (2) Principles and Principles of multicultural-based education curriculum preparation. This research is designed in the form of library research. The results of this study concluded that (1) classification of Multicultural Based Curriculum from three points of view, namely First: Concept and Implementation Perspective is classified into 3 namely (a) Ideal Curriculum (b) Factual Curriculum, and (c) Hidden Curriculum. Second: The Structure and Subject Matter Perspective is classified into 4 i.e. (a) Sparated Curriculum. (b) Broad Fields Curriculum (c) and. (4) Integrated Curriculum. Third: The Scope of Use perspective is classified into 3 i.e. (a) national curriculum, (b) state curriculum,(c) and school curriculum. (2) Principles in designing a multicultural-based curriculum namely (a) The Principle of Child Psychology, (b) the Principle of National Sociology, (c) the Principle of Development of World Science and Technology, and (d) the Principle of Pancasila as the Philosophy of the Nation. While the Principles of Curriculum Preparation in Multicultural Education include: (a) relevance principle, (b) flexibility, (c) continuity, (d) efficient, and (e) effective.